THU0352 DIAGNOSTIC PERFORMANCES OF HAND ULTRASOUND PARAMETERS AND THEIR IMPACT ON THE 2013 ACR/EULAR CLASSIFICATION CRITERIA FOR SYSTEMIC SCLEROSIS. (2nd June 2020) - De Saint Riquier, M.; Ballerie, A.; Robin, F.; Belhomme, N.; Cazalets, C.; Droitcourt, C.; Perdriger, A.; Yelnik, C. M.; Hachulla, E.; Sobanski, V.; Jégo, P.; Coiffier, G.; et al.
Abstract : Background: Recent studies have highlighted that ultrasound (US) examination could offer a better assessment of hand manifestations of systemic sclerosis (SSc). Indeed, US allows a simultaneous evaluation of vascular, fibrotic and inflammatory hand features of the disease. Power Doppler US can especially explore macrovascular involvement characterized by an obliteration of digital arteries or ulnar arteries. Ulnar artery occlusion (UAO) is especially frequent in SSc patients and could be a relevant marker of the severity of SSc-associated vasculopathy. Among other hand manifestations of SSc, US evaluation can notably explore tenosynovial involvement such as fibrotic tenosynovitis (TS), which is considered to be SSc-specific. Objectives: This study aims to assess the diagnostic performances of these hand US parameters for the diagnosis of SSc. Methods: 244 patients with suspected SSc were consecutively included. They all had US evaluation assessing the presence of fibrotic TS and UAO. The final diagnosis of SSc was based on the evaluation of an expert, independently from US results and from any pre-established classification criteria. Results: 166 patients were finally diagnosed as SSc. 62 SSc and 8 non-SSc patients had UAO (uni or bilateral) (p=0.001). 23 SSc patients and 1 non-SSc patient had US fibrotic TS (p=0.007). A US SSc-pattern (presence of UAO and/or fibrotic TS) was reported in 73 SSc patients and 9 non-SSc patients (p<0.001). UAO had an area under ROC curve (AUC) for the diagnosis of SSc of 0.618 (95%CI 0.539-0.697); with Se= 0.373 (0.304-0.449) and spe=0.862 (0.751-0.928). The presence of a US fibrotic TS had an AUC of 0.561 (0.480-0.643); with Se= 0.139 (0.094-0.199) and spe=0.983 (0.909-0.997). The US-SSc pattern had a AUC of 0.641 (0.563-0.695), with Se=0.440 (0.367-0.516) and spe=0.845 (0.731-0.916). When used as a diagnostic tool, the original 2013 classification criteria had an AUC of 0.982 (0.969-0.996) with Se= 0.946 (0.900-0.971) and spe=0.931 (0.836-0.973). Including UAO and fibrotic TS in this classification had few impact (AUC of 0.979 (0.962-0.996) with Se= 0.940 (0.893-0.967) and and spe=0.931 (0.836-0.973)) but allows the substitution of some items (such as capillaroscopy) by US parameters with similar performances for diagnosis. Conclusion: The use of hand US parameters may help to refine the diagnostic strategy of SSc and their inclusion in addition with the items of the ACR/EULAR classification could be discussed. Disclosure of Interests: Marine de Saint Riquier: None declared, Alice Ballerie: None declared, François ROBIN: None declared, Nicolas Belhomme: None declared, Claire Cazalets: None declared, Catherine Droitcourt: None declared, Aleth Perdriger: None declared, Cécile Marie Yelnik: None declared, Eric Hachulla Speakers bureau: speaking fees from Actelion Pharmaceuticals, GlaxoSmithKline, and Bayer outside of the current study, Vincent Sobanski: None declared, Patrick Jégo: None declared, Guillaume Coiffier: None declared, Alain LESCOAT: None declared